Comparison of Massage and Ice Massage on Delayed Onset Muscle Soreness in Hamstring Muscles Following Lying Leg Curl Exercise - Amiruddin Dwi Atmaja (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to analyze the comparison between massage and ice massage interventions in preventing pain caused by delayed onset muscle soreness (DOMS) in the hamstring muscles after lying leg curl exercise. The study also examined the effectiveness differences between both physiotherapy treatments in reducing post-exercise muscle pain. Methodology: This study used a quasi-experimental method with a pre-test and post-test two-group design. The sampling technique employed purposive sampling involving 20 students. Pain intensity was measured using the Visual Analog Scale (VAS). Data analysis utilized paired sample t-test and independent sample t-test to compare the effectiveness of massage and ice massage interventions. Main Findings: The findings showed that both massage and ice massage significantly reduced pain caused by delayed onset muscle soreness after lying leg curl exercise. Statistical analysis indicated significant effects in both intervention groups with p-values below 0.05. Furthermore, there was a significant difference between massage and ice massage interventions, where ice massage demonstrated a more effective reduction in hamstring muscle pain intensity. Novelty/Originality of this study: This study provides a comparative analysis between massage and ice massage specifically for preventing DOMS in hamstring muscles after lying leg curl exercise. The originality lies in the direct comparison of two physiotherapy interventions within exercise recovery management, contributing practical evidence for physiotherapists, sports practitioners, and rehabilitation programs in selecting effective post-exercise recovery methods.